Factors affecting customers' adoption of internet banking in Afghanistan - Wasiq, Shafiullah; Othman, Marini; Abdullah, Zainatul Shima (IEEE, 2022)
In recent decades advances in technology have changed the banking industry. The advancement of e-commerce and e-society is dependent on electronic banking, particularly internet banking. This rapid advancement of computer technology, especially the internet, has enabled the banking industry to provide services to customers more efficiently and efficiently. However, the main problem of Internet banking faced by internet banking providers in Afghanistan is that many of the banks' customers are unwilling to adopt the Internet banking services offered. This happened due to various factors. This can be because of customers' personal experiences, awareness, level of internet access, and diverse socio-cultural backgrounds. Therefore, this research aims to identify the factors that affect customers' adoption of internet banking in Afghanistan. In this study, the factors which can influence customer adoption of Internet banking include perceived usefulness, perceived ease of use, attitude, and intention. In this study, a survey questionnaire was distributed among 184 Afghan participants and provided valuable feedback and responses about the above factors that affect customers' adoption of Internet banking. The results from this study indicated that among the studied variables, perceived usefulness, ease of use, attitude, and intention were closely linked to internet banking adoption in Afghanistan. The results of the present study may provide valuable practical implications for banks and financial industries. It also helps banks to understand the significant factors in providing efficient internet banking services to the Afghan community.